Practising Chemistry in the British Empire: George Christian Hoffmann (1837-1917) and the Geological Survey of Canada - Rae, Ian; Maroske, Sara (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2021)
George Christian Hoffmann, of German extraction, was born in London. After studying at the Royal School of Mines and working in London as a chemical analyst, he set out on a career that took him to Natal, in south-east Africa, to Melbourne in the Australian colony of Victoria, and to Canada where he had a long career with the Geological Survey, becoming Deputy Director in 1880 and retiring in 1907. In his work with the Geological Survey, he determined the chemical composition and identity of mineral samples collected by and submitted to the Survey, assessing their economic potential.